Associations between air pollution and markers of neuroinflammation, synaptic dysfunction and core Alzheimer’s disease pathology vary by APOE genotype - Kana Kimura; Ira Driscoll; Noah Cook; Sonia Shahzad; Tobey J. Betthauser; Sterling C. Johnson; Sanjay Asthana; Catherine L. Gallagher; Bruce P. Hermann; Mark A. Sager; Kaj Blennow; Henrik Zetterberg; et al. (Neurotoxicity Research, 2026)
To determine whether long-term residential air pollution [AP; ozone (O₃) and fine particulate matter (PM₂.₅)] is associated with (1) incident mild cognitive impairment (MCI) or Alzheimer’s disease (AD), (2) biomarkers of core and AD-relevant pathology, and (3) whether these relationships are moderated by APOE4+/- (carrier/non-carrier of one or both ε4 alleles) status or mediated by neuroinflammation. Sample included 795 participants (Mage 68.7 ± 7.9; 68% female) from the Wisconsin Alzheimer’s Disease Research Center and Wisconsin Registry for Alzheimer’s Prevention parent studies, both enriched for AD risk at enrollment based on parental AD history. Residential zip code and 2009–2021 EPA-based annual AP reports were used to estimate individual exposure. Cox proportional hazards models assessed MCI/AD risk. Linear regressions examined the relationships between AP exposure and biomarkers of core and AD-relevant pathology, with and without APOE4 + stratification. Causal mediation analysis examined whether markers of inflammation mediated the AP-AD pathology relationships. Neither O₃ nor PM₂.₅ exposure predicted MCI/AD incidence nor core AD pathology (Ps > 0.05). Higher PM₂.₅ was associated with higher CSF GFAP levels ( P = 0.003). APOE4 + with higher levels of PM₂.₅ exposure had higher CSF levels of tTau ( P = 0.01), pTau₁₈₁ ( P = 0.01) and neurogranin ( P = 0.02). These relationships were not mediated by neuroinflammation (Ps > 0.05). In this AD-risk enriched cohort, AP was not associated with MCI/AD incidence. However, higher PM₂.₅ exposure was associated with astrocytic activation, and in APOE4+, AD pathology, neurodegeneration, and synaptic dysfunction. Our findings suggest AP as an environmental risk factor contributing to AD-relevant pathology, particularly among genetically at-risk individuals.